Community-Level Effects of Garlic Mustard Invasion on Wisconsin Forest Communities - Riddle, Anne A. (My University, 2008)
Community ecologists frequently assume that impacts of invasive species are negative, but this assertion is poorly supported in the literature. To test this, we surveyed 10 sites invaded with the biennial herb Alliaria petiolata (M. Bieb) Cavara and Grande and 3 uninvaded paired sites and tested species diversity between them. We found no significant differences in species diversity between the sites, thereby questioning the hypothesis that invasion causes biodiversity loss. Low biodiversity was instead correlated with human activity, suggesting that niche availability drives invasion in these sites. Nonetheless, invasion "time lag" may be a factor in these sites and long-term, established study is needed to determine effects of the garlic mustard over time.
13 p.
Keywords: Horticulture; Botany